2017
DOI: 10.1127/anthranz/2017/0680
|View full text |Cite
|
Sign up to set email alerts
|

Regular graveyard in the stronghold versus settlement burials in the bailey. Comparison of Early Medieval populations from Pohansko (Czech Republic)

Abstract: The aim of the study is to identify possible differences in the prevalence of biological stress markers (cribra orbitalia, linear enammel hypoplasia), dental caries, activity markers (Schmorl's nodes) and markers of violence (traumatic lesions) in populations from a typical graveyard around the first church (9-10 century AD) in the stronghold and from settlement burials in the southern bailey (second half of the 9 - beginning of the 10 century AD) of Slavs from Pohansko (Czech Republic). Cribra orbitalia and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Additionally, the prevalence of cribra orbitalia reported in these modern populations were 24.3% (O'Donnell et al, 2020), 29.6% (Hens et al, 2019), and 33.3% (Rothschild et al, 2021), similar to prevalence reported in many populations across time and around the world (Bečić et al, 2014; Blom et al, 2005; Carlson et al, 1974; Gibbon & Davies, 2020; Juengst et al, 2017; Kalová et al, 2017; Kozak & Krenz‐Niedbała, 2002; Kyle et al, 2018; Lallo et al, 1977; Łubocka, 2000; Nathan et al, 1966; Novak, 2011; Okumura & Eggers, 2005; Redfern et al, 2015; Yaussy et al, 2016; Zhang et al, 2016).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Additionally, the prevalence of cribra orbitalia reported in these modern populations were 24.3% (O'Donnell et al, 2020), 29.6% (Hens et al, 2019), and 33.3% (Rothschild et al, 2021), similar to prevalence reported in many populations across time and around the world (Bečić et al, 2014; Blom et al, 2005; Carlson et al, 1974; Gibbon & Davies, 2020; Juengst et al, 2017; Kalová et al, 2017; Kozak & Krenz‐Niedbała, 2002; Kyle et al, 2018; Lallo et al, 1977; Łubocka, 2000; Nathan et al, 1966; Novak, 2011; Okumura & Eggers, 2005; Redfern et al, 2015; Yaussy et al, 2016; Zhang et al, 2016).…”
Section: Discussionsupporting
confidence: 59%
“…Such intra‐study assessments, again, reveal similar prevalence among disparate populations. For example, Kyle et al (2018) document a prevalence of 28.4% in Greek Himera (33.3% from soldiers found in graves from the battles of Himera‐ 480 and 409 BC and 27.8% from Himeran civilians from 648 to 409 BC); Kalová et al (2017) note prevalence such as 32%, 26%, 32.8%, 20.8%, 25.8% from varied Slavic populations from different sites in the 9th–10th centuries AD and a prevalence of 26.6% in an 11th–12th century sample; Yaussy et al (2016) document a prevalence of 33.1% among individuals in an attritional burial type and 36.6% among individuals in a famine burial type from the St. Mary Spital cemetery, London, England dating from 1,120–1,540 AD; Redfern et al (2015) document a prevalence of 23 and 26% of urban and rural populations from Dorset England dating from the first‐fifth centuries AD (mostly the fourth century). Nathan et al (1966) describe similar prevalence in various geographical‐ethnical groups from North America, Central America, Europe, and Asia that include prevalence among 20% of “Eskimo” from Alaska (USA); 21.6% of “Indians” from Mexico; 23% of individuals from Austria; 25% of individuals from the Canary Islands; and 21.5% of individuals from the Malayan Peninsula (Singapore).…”
Section: Discussionmentioning
confidence: 99%